A System Dynamics Approach to ERP Adoption in SMEs: A Case Study of Banyumas - ramdhani, ade yanyan; Lina Fatimah Lishobrina; Alon Tirta Jala Segara; Halim Qista Karima1b; Bachtiar Herdianto (Program Studi Teknik Industri Universitas Pembangunan Nasional Veteran Jawa Timur, 2025)
Small and Medium Enterprises (SMEs) are pivotal to economic development, particularly in Indonesia, where they contribute significantly to employment and Gross Domestic Product (GDP). However, the adoption of sophisticated technologies such as Enterprise Resource Planning (ERP) systems remains a challenge due to constraints in resources, resistance to change, and implementation costs. This study applies a system dynamics methodology to develop an ERP adoption model specifically tailored for SMEs in Banyumas. The model synthesizes mental models derived from a comprehensive review of literature and semi-structured interviews with relevant stakeholders, culminating in the creation of a Causal Loop Diagram (CLD). This diagram identifies key feedback loops influencing ERP adoption, including reinforcing loops related to awareness and business benefits, and balancing loops that address implementation challenges such as cost and complexity. The findings underscore the critical role of government support, the development of cost-effective ERP solutions, and the importance of training programs in facilitating ERP adoption. The proposed model provides practical insights for policymakers and ERP providers to enhance digital transformation within SMEs.